Analisis Keunggulan Bersaing Terhadap Kinerja Bisnis Yang Berkelanjutan (Studi Kasus Yayasan Sekolah Daya Utama Kota Bekasi) - Doddy Sukma Wirawan (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
This research is about the Analysis of Competitive Advantage on Sustainable Business Performance. The purpose of this study was to determine the effect of organizational capability and innovation to achieve competitive advantage on sustainable business performance (a study at the Daya Utama School Foundation in Bekasi City). Engaged in education starting from elementary, junior high, high school and vocational education levels. The sampling technique uses purposive sampling, amounting to 30 respondents. Data collection using a questionnaire. Data analysis techniques using Structural Equation Modeling (SEM) analysis which is processed with Smart PLS 2.0. The results of the study prove that organizational capability has a positive and significant effect on competitive advantag , Innovation has a positive and significant effect on competitive advantage, Organizational capability has a positive and significant effect on sustainable business performance, Innovation has a positive and significant effect on sustainable business performance, Competitive advantage has a positive and significant effect on the sustainable business performance of School Daya Utama Foundation at Bekasi City.